Deep Learning Opportunities in Progressive Islamic Education - Baktiar Nasution; Adirasa Hadi Prasetyo; Ayuba Olaniyi Jibril; Decky Saputra (Pascasarjana Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2024)
Internalization of Islamic teachings must be carried out by educators to students in a deep and meaningful way. This meaningful learning process must be able to present a process that is enjoyable for students. This study aims to find a correlation between the concept of Deep Learning and its application to Islamic education materials. This research method uses Literature Review with the help of the Harzing Publish or Perish application. There are 10 articles on Deep Learning that are relevant and can be applied to Islamic religious education. The main findings of this study state that Deep Learning is very suitable for application in Islamic religious education which has heterogeneous and varied fields of study. The significance of this research is to provide additional new knowledge for academics and education practitioners, especially in the field of Islamic education, to apply deep learning in a meaningful and joyful in the learning process.